Effect of production factors and ripening conditions on the characteristics of Serra cheese - Macedo, Angela C. (2011)
The individual and interactive effects of four production factors (amount of vegetable rennet, temperature of coagulation, pressing and salting of the fresh cheese) and two ripening factors (temperature and relative humidity) on microbiological, physico-chemical, biochemical, textural and sensory characteristics of Serra cheese were simultaneously studied using a 2vi6-1 factorial design. Highly significant effects of salting and ripening relative humidity upon the characteristics of the cheese were detected. Addition of salt to the surface of the fresh cheese reduced microbial growth, water activity, moisture and lactic acid contents, proteolysis, lipolysis, aroma and softness of the cheese. Conversely, increase of the relative humidity during ripening increased these charactereristics. Pressing had no statistically significant effect on cheese characteristics.